The deserted library mystery - Warner, Gertrude Chandler, 1890-1979; Tang, Charles (Morton Grove, Ill. : A. Whitman, 1991)
At an old library, the Alden children discover a boy who needs their help and a stranger who is after a valuable object they found in the library.
4.9
3-6.
Keywords: Boxcar children (Fictitious characters) -- Juvenile fiction; Orphans -- Juvenile fiction; Families -- Juvenile fiction; Mystery and detective stories; Libraries -- Fiction; Libraries -- Fiction; Mystery fiction; Detective and mystery stories